Genetic screening of a large series of North American sporadic and familial frontotemporal dementia cases. Issue 1 (8th January 2020) - Ramos, Eliana Marisa; Dokuru, Deepika Reddy; Van Berlo, Victoria; Wojta, Kevin; Wang, Qing; Huang, Alden Y.; Deverasetty, Sandeep; Qin, Yue; van Blitterswijk, Marka; Jackson, Jazmyne; Appleby, Brian; Bordelon, Yvette; et al.
Abstract: Introduction: The Advancing Research and Treatment for Frontotemporal Lobar Degeneration (ARTFL) and Longitudinal Evaluation of Familial Frontotemporal Dementia Subjects (LEFFTDS) consortia are two closely connected studies, involving multiple North American centers that evaluate both sporadic and familial frontotemporal dementia (FTD) participants and study longitudinal changes. Methods: We screened the major dementia‐associated genes in 302 sporadic and 390 familial (symptomatic or at‐risk) participants enrolled in these studies. Results: Among the sporadic patients, 16 (5.3%) carried chromosome 9 open reading frame 72 ( C9orf72 ), microtubule‐associated protein tau ( MAPT ), and progranulin ( GRN ) pathogenic variants, whereas in the familial series we identified 207 carriers from 146 families. Of interest, one patient was found to carry a homozygous C9orf72 expansion, while another carried both a C9orf72 expansion and a GRN pathogenic variant. We also identified likely pathogenic variants in the TAR DNA binding protein ( TARDBP ), presenilin 1 ( PSEN1 ), and valosin containing protein ( VCP ) genes, and a subset of variants of unknown significance in other rare FTD genes. Discussion: Our study reports the genetic characterization of a large FTD series and supports an unbiased sequencing screen, irrespective of clinical presentation or family history.